Pan-Cancer Analysis Identified CD93 as a Valuable Biomarker for Predicting Patient Prognosis and Immunotherapy Response - Tong, Wen; Wang, Guangyu; Zhu, Liuyang; Bai, Yi; Liu, Zirong; Yang, Long; Wu, Hao; Cui, Tao; Zhang, Yamin (Frontiers in Molecular Biosciences, 2022)
Background: With the rapid development of immunotherapy, it has significantly improved patient outcomes in recent years. CD93, a novel biomarker expressed on vascular endothelial cells, is essential for tumor angiogenesis. Recent studies have shown that CD93 is closely related to immune cell infiltration and immunotherapy. However, its role in pan-cancer has not been reported. Methods: TCGA, HPA, cbioportal, GEO, TIMER2.0, TISIDB databases were used to analyze CD93 in pan-cancers. R software was used for statistical analysis and mapping. Results: There were significant differences in the expression of CD93 between tumor tissues and adjacent normal tissues in pan-cancer. The high expression of CD93 is associated with poor prognosis and high TNM stage in multiple tumor types. However, high expression of CD93 is a protective factor in KIRC. In addition, CD93 is closely related to immune cell infiltration in tumor tissues. Moreover, CD93 presented a robust correlation with immune modulators, and immunotherapeutic markers (TMB and MSI). GSEA results showed that CD93 was correlated with tumor angiogenesis. Importantly, patients with low expression of CD93 are more sensitive to immunotherapy in Urothelial cancer. Conclusion: CD93 involved in various immune responses, controls immune cell infiltration, and impacts malignant properties of various cancer types. Therefore, CD93 has potential value to be biomarker to determine the prognosis and immune infiltration in multiple cancers.